عصمتِ محمدی ﷺ پر شبہات اور ان کا ازالہ: Doubts over the infallibility of the Personality of Muhammad (PBUH) and their refutation” - Muhammad Farooq Abdullah; Dr. Muhammad Abdullah (MEI, 2023)
Muslims unanimously believe that the Qur'an is the last book of the Almighty, free from all imperfections. This is the true word of Almighty Allah and no distortion is possible in it. Muhammad is the servant and last messenger of Allah. The Qur'an defends the protection of the infallibility of all the prophets. Deniers of the Holy Prophet (PBUH), including some Orientalists, etc., raise some doubts and objections against the personality of Holy Prophet (PBUH) from some verses of the Holy Qur'an. Their purpose is to make the Prophet's prophet-hood and infallibility doubtful in the eyes of unaware and unknowing people. In the light of Islamic teachings, all the prophets and messengers are infallible and innocent, and no sin can be committed by them, so how can Islam tolerate insulting or degrading of other prophets۔ Therefore the humiliation of Muhammad's blessed personality is intolerable because he himself is the protector of the infallibility of all the prophets. This article will examine some of these doubts as well as answer them through the Qur'an, Sunn'ah and the commentators, which are accused by the orientalists on the personality of Holy Prophet Muhammad (PBUH).